Near Real Time Network Simulation for Team Sports Monitoring - James, D. A.; Fanella, L.; Cusani, R. (Procedia Engineering, 2013)
On field monitoring of athlete performance is a growing area of interest in elite, professional and even some amateur sports. Metrics routinely monitored can be tactical, physiological and biomechanical, some methods are more labor intensive than others such as bloods and video coded and hand scored performance data. More recently the introduction of wearable sensors and GPS have allowed comparatively large amounts of data to be collected. These sensors are changing the way athletes are assessed, and today are routinely used by a number of professional football codes. Near real time systems, have been shown to enable the information to be accessed more quickly and thus the data can be used tactically, for workload management during game play, in addition to post game analysis. On e of the major challenges is to have robust wireless network solutions for this challenging environment. This paper implements a number of player based network topologies and protocols in a simulation environment to test various scenarios, as a tool for future development. Performance limitations to throughput and goodput are used to identify potential bottlenecks. Because the construction of physical hardware devices for athletes and networks, simulation is an attractive process that can shorten development time, identify and solve design problems more rapidly. These tests are intended as an input to designing better devices, networks and thus optimizing ambulatory systems for range, battery life and size reduction.